On-campus pocket parks for enhancing outdoor learning experience in Malaysian universities\ - Abdulkareem Salih, Sarah; Ismail, Sumarni; Ismail, Nor Atiah (Human Resource Management Academic Research Society, 2021)
Recently, small nearby outdoor spaces have become an important tool to improve academic outcomes by enhancing students' social-learning experience. However, nearby open spaces and pocket parks of Malaysian universities lack the absorption of informal and formal outdoor education that may affect the academic experience, especially in the outdoor spaces. Therefore, there is a need to enhance students' on-campus learning experience in Malaysian universities. This study aimed to investigate the visually preferred pocket parks criteria to promote students' learning experience on Malaysian campus grounds; this is in line with the Twelfth Malaysia Plan for 2021-2025. This study employed a visual-verbal preference survey (VVPS) conducted in three Malaysian universities, including Universiti Malaya (UM), Universiti Putra Malaysia (UPM), and Universiti Kebangsaan Malaysia (UKM), to assess the visual preferences of 415 students toward six pocket parks sceneries. Multiple regression analysis was used to predict the relationship between students' outdoor learning experience and preferred pocket parks criteria. The result showed that pocket parks that provide a strong shade, variety in softscape and activities, and bench hardscape contributed to enhancing students' outdoor learning. The result indicated that providing on-campus pocket parks with the preferred design criteria can enhance the learning experience. Thus, the current study contributed to integrating nearby pocket parks in outdoor learning to improve campus urban design and academic experience. The study's findings are of great importance for policymakers and academic administration, landscape and urban planners, and researchers in the field in creating an academically responsive campus.